Method for the measurement of triboelectric charge transfer at solid–liquid interface - Qin Chen; Bingxue Cheng; Tiancheng Wang; Hongfei Shang; Tianmin Shao (Friction)
Abstract Triboelectrification between a liquid and a solid is a common phenomenon in our daily life and industry. Triboelectric charges generated at liquid/solid interfaces have effects on energy harvesting, triboelectrification-based sensing, interfacial corrosion, wear, lubrication, etc. Knowing the amount of triboelectric charge transfer is very useful for studying the mechanism and controlling these phenomena, in which an accurate method is absolutely necessary to measure the triboelectric charge generated at the solid—liquid interface. Herein, we established a method for measuring the charge transfer between different solids and liquids. An equipment based on the Faraday cup measurement was developed, and the leakage ratio (r l) was quantified through simulation based on an electrostatic field model. Typical experiments were conducted to validate the reliability of the method. This work provides an effective method for charge measurement in triboelectrification research.